2021
DOI: 10.1080/20009666.2020.1854417
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone induced pulmonary edema

Abstract: Naloxone-induced noncardiogenic pulmonary edema is a rare but reported entity that can occur following naloxone use in the reversal of opioid overdose. Proposed mechanisms include an adrenergic crisis secondary to catecholamine surge which causes more volume shift to pulmonary vasculature, subsequently leading to pulmonary edema. It appears to be more common when higher doses of naloxone are used. We present a case of a patient with opioid overdose came with altered mental status developed early features of pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…In the event of an opioid overdose, naloxone may have adverse effects, albeit clinical data indicate that serious events are rare. 3,[41][42][43][44][45][46] In case of individuals with an opioid use disorder, withdrawal symptoms may become apparent after naloxone administration; symptoms include tachycardia, mild agitation or anxiety, hypertension abdominal pain, malaise, and insomnia. 2,3,41 In extremely rare cases, abrupt reversal of opioid-induced respiratory depression by naloxone has been followed by seizures, pulmonary edema, cardiac dysrhythmias, hypertension, and cardiac arrest.…”
Section: Naloxone Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…In the event of an opioid overdose, naloxone may have adverse effects, albeit clinical data indicate that serious events are rare. 3,[41][42][43][44][45][46] In case of individuals with an opioid use disorder, withdrawal symptoms may become apparent after naloxone administration; symptoms include tachycardia, mild agitation or anxiety, hypertension abdominal pain, malaise, and insomnia. 2,3,41 In extremely rare cases, abrupt reversal of opioid-induced respiratory depression by naloxone has been followed by seizures, pulmonary edema, cardiac dysrhythmias, hypertension, and cardiac arrest.…”
Section: Naloxone Safetymentioning
confidence: 99%
“…Vasoconstriction and an increase in blood pressure and the occurrence of tachyarrhythmias may be the basis of these complications, with pulmonary edema arising from a rapid fluid shift or from inspiration against a closed glottis (negative pressure pulmonary edema). 3,46 Complications may be enhanced when the patient is in a circulatory unstable condition such as low blood pressure from opioid-induced vasodilation or in case of a high vasomotor tone from (psychologic) stress, agitated delirium and/or pain. 3 In the event of complications, it is crucial to treat the different symptoms and reduce the elevated sympathetic activity with an α 2 -adrenergic receptor agonist.…”
Section: Naloxone Safetymentioning
confidence: 99%
“…For example, Gordon and Pellino57 reported that 21% of their patients who receive naloxone were subsequently diagnosed with another condition (eg, pneumonia, acute renal failure), which could have contributed to their clinical decline. Administration of a large dose of naloxone, especially to surgical patients, is not without risks, as catecholamine surge reverses opioid analgesia, which has been linked to pulmonary edema, and rather smaller doses of naloxone titrated to effect, if situation permits, is advisable 57,65–67. Alternatively, unresponsiveness to naloxone treatment could be in situations when RD has progressed to the point where clinical intervention with naloxone has become futile 45…”
Section: Incidence Of Rd Among Hospitalized Patientsmentioning
confidence: 99%
“…36 More worrisome is that the protocols regarding the timing of these vital sign checks, especially among higher risk patients who are prescribed more frequent assessments, are often not followed. 66 In part, the inability to perform more frequent vital sign checks is driven by economic restraints, which dictate lower nursing-topatient staffing levels on general care wards. 105 While continuous electronic monitoring has been recognized as superior to intermittent vital sign checks, 36 the cost and size of such monitors have been prohibitive for widespread use on general care wards.…”
Section: Postoperative Monitoringmentioning
confidence: 99%
“…Acute opioid withdrawal is associated with anxiety, piloerection, yawning, sneezing, rhinorrhea, nausea, vomiting, diarrhea, and abdominal or muscle cramps. Naloxone-induced noncardiogenic pulmonary edema has been reported rarely and appears to be more common when higher doses are used …”
Section: Adverse Effectsmentioning
confidence: 99%